Factors Affecting the Intention to Buy Electric Vehicles Through the Integration of Technology Acceptance Model and Prior Experience - Saleh, Hendra Noor; Maupa, Haris; Cokki, Cokki; Sadat, Andi Muhammad (Bright Publisher, 2025)
To enhance the adoption of electric vehicles (EVs), governments have implemented regulatory policies, such as providing incentives. However, this approach is temporary and relies on the active involvement of manufacturers to better understand the driving factors behind EV adoption. While previous studies, largely based on behavioral theory, emphasize psychological and environmental factors, individual subjective factors also play a crucial role. This study introduces a novel approach by integrating variables from the Technology Acceptance Model (TAM)—perceived usefulness and perceived ease of use—with consumer experience variables, namely technology discomfort and customer experience. The goal is to improve TAM's explanatory power regarding the intention to buy EVs from the consumer perspective. The research targeted residents of Jabodetabek (Jakarta, Bogor, Depok, Tangerang, Bekasi) aged 17 and older, all of whom had prior experience with Battery Electric Vehicles (BEVs). Data was collected from 330 respondents through an online survey. Structural Equation Modeling (SEM) with AMOS was used for the analysis. The results indicated that perceived usefulness, perceived ease of use, and customer experience significantly influenced intention to buy, while perceived usefulness did not significantly affect customer experience. Customer experience mediated the relationship between perceived ease of use and intention to buy, but did not mediate the effect of perceived usefulness. Additionally, technology discomfort negatively impacted perceived usefulness and ease of use, although it did not significantly affect customer experience. These findings suggest that while government incentives remain important, a market-driven approach that focuses on improving consumer perceptions and experiences is critical for accelerating EV adoption.